1999
DOI: 10.1007/pl00005815
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of a New Immunoradiometric Assay for Intact Human Osteocalcin

Abstract: The purpose of this study was to estimate clinical validity of a new available immunoradiometric assay for circulating intact human BGP (N-tact Osteo SP) by measuring this protein in a large number of normal subjects and patients with the most common metabolic bone diseases. One hundred normal subjects were studied in order to obtain our normal ranges (4.9 +/- 1.7 ng/ml). The mean values found in 28 patients with primary hyperparathyroidism (17.5 +/- 22.8 ng/ml, P < 0.001), 15 glucocorticoid-treated patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…A few studies have shown that bone turnover marker levels are frankly low or low‐normal in patients with hypoparathyroidism compared to normal subjects, and these findings are consistent with histomorphometric analysis. In particular, double tetracycline labelling of bone biopsy specimens has demonstrated that dynamic skeletal indices are suppressed in hypoparathyroid patients .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A few studies have shown that bone turnover marker levels are frankly low or low‐normal in patients with hypoparathyroidism compared to normal subjects, and these findings are consistent with histomorphometric analysis. In particular, double tetracycline labelling of bone biopsy specimens has demonstrated that dynamic skeletal indices are suppressed in hypoparathyroid patients .…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, despite significant changes in bone turnover, teriparatide did not provide any significant BMD improvement in hypoparathyroidism . In particular, after 3 years of twice daily PTH treatment, BMD and bone mineral content (BMC) at the lumbar spine, femoral neck and whole body remained stable although there was a nonsignificant downward trend in BMD at the distal radius.…”
Section: Discussionmentioning
confidence: 93%
“…12 Moreover, lack of a standardized commercial assay complicates comparison of concentrations among studies. 13 Undercarboxylated osteocalcin (ucOC) is a precise indicator of vitamin K status. It reflects vitamin K's role in carboxylating glutamic acid residues on the protein that subsequently facilitates the binding of OC to hydroxyapatite in bone.…”
Section: Introductionmentioning
confidence: 99%
“…Bone isoenzyme of alkaline phosphatase (BALP) was determined with an immunoenzymatic assay (Metra BAP EIA Kit, Quidel Corporation, San Diego, CA, USA) (Gomez et al, 1995); intraand inter-assay coefficients of variation were less than 5AE6 and 7AE8% respectively. Serum osteocalcin (BGP) was determined with an immunoradiometric assay (BGP; N-tact Osteo SP, DiaSorin, Stillwater, MN, USA) (Minisola et al, 1999); intraand inter-assay coefficients of variation were less than 4AE5 and 9AE5% respectively. Bone sialoprotein (BSP) was determined using a radioimmunoassay (Immunodiagnostik AG, Bensheim, Germany) described elsewhere (Karmatschek et al, 1997).…”
Section: Laboratory Methodsmentioning
confidence: 99%